Induksi Perakaran Tunas Tetrastigma rafflesiae Miq. Pada Media Murashige-Skoog Dengan Penambahan Beberapa Konsentrasi Indole-3-Butyric Acid (IBA) secara In Vitro - Erni Febriyanti; - Suwirmen; M. Idris (Jurnal Biologi Universitas Andalas, 2013)
An experiment on in vitro root induction of Tetrastigma rafflesiae Miq. on Murashige-Skoog (MS) medium supplemented with several concentrations of Indole-3-Butyric Acid (IBA) had been done from February to April 2013. The aims of this experiment was to determine physiological responses of T. rafflesiae’s shoot to the IBA on half strength media of MS for root induction stages. The experiment used a completely randomized design in seven treatments and four replications. The treatment was the addition of IBA in several concentration (i.e. 0.0; 0.5; 1.0; 1.5; 2.0; 2.5 and 3.0 mg/l). The results showed 0.5 mg/l supplemented IBA was more effective and efficient in root induction of shoot then other concentrations. It influenced the average number of roots (12.5 root/plantlet), the average length of root (4.98 cm) and the morphological of plantlets. The result indicated that plantlet of T. rafflesiae generated in in vitro had a higher possibility of artificial culture and prospective for future conservation of Rafflesia.Keywords : Tetrastigma rafflesiae Miq., root induction, Indole-3-Butyric-acid.